Impact of methamphetamine on infection and immunity - Salamanca, Sergio A.; Sorrentino, Edra E.; Nosanchuk, Joshua D.; Martinez, Luis R. (Frontiers in Neuroscience, 2015)
The prevalence of methamphetamine (METH) use is estimated at ~35 million people worldwide, with over 10 million users in the United States. METH use elicits a myriad of social consequences and the behavioral impact of the drug is well understood. However, new information has recently emerged detailing the devastating effects of METH on host immunity, increasing the acquisition of diverse pathogens and exacerbating the severity of disease. These outcomes manifest as modifications in protective physical and chemical defenses, pro-inflammatory responses, and the induction of oxidative stress pathways. Through these processes, significant neurotoxicities arise, and, as such, chronic abusers with these conditions are at a higher risk for heightened consequences. METH use also influences the adaptive immune response, permitting the unrestrained development of opportunistic diseases. In this review, we discuss recent literature addressing the impact of METH on infection and immunity, and identify areas ripe for future investigation.